Mesenchymal Stem Cells Subpopulations: Application for Orthopedic Regenerative Medicine - Vanessa Pérez-Silos; Alberto Camacho-Morales; Lizeth Fuentes-Mera (Stem Cells International)
Research on mesenchymal stem cells (MSCs) continues to progress rapidly. Nevertheless, the field faces several challenges, such as inherent cell heterogeneity and the absence of unique MSCs markers. Due to MSCs’ ability to differentiate into multiple tissues, these cells represent a promising tool for new cell-based therapies. However, for tissue engineering applications, it is critical to start with a well-defined cell population. Additionally, evidence that MSCs subpopulations may also feature distinct characteristics and regeneration potential has arisen. In this report, we present an overview of the identification of MSCs based on the expression of several surface markers and their current tissue sources. We review the use of MSCs subpopulations in recent years and the main methodologies that have addressed their isolation, and we emphasize the most-used surface markers for selection, isolation, and characterization. Next, we discuss the osteogenic and chondrogenic differentiation from MSCs subpopulations. We conclude that MSCs subpopulation selection is not a minor concern because each subpopulation has particular potential for promoting the differentiation into osteoblasts and chondrocytes. The accurate selection of the subpopulation advances possibilities suitable for preclinical and clinical studies and determines the safest and most efficacious regeneration process.